Biophysical Habitat Features Explain Colonization and Size Distribution of Introduced Trochus (Gastropoda) - Seinor, Kate M.; Smith, Stephen D. A.; Logan, Murray; Purcell, Steven W. (Frontiers in Marine Science, 2020)
The trochid gastropod, Rochia nilotica is harvested in small-scale fisheries throughout Southeast Asia and the Pacific Islands, many of which were created from inter-country translocations. This species is found on structurally complex shallow reefs, but specific habitat requirements have not yet been quantified in order the maximize the success of future translocations and help future-proof the fishery in changing ocean conditions. At 28 sites around Samoa, where the species was introduced in the early 2000s, we measured a suite of habitat variables along transects in which R. nilotica were counted and the shell sizes measured in a parallel study. Boosted regression tree analyses revealed that R. nilotica were most abundant at reef locations that were shallow, with fairly consistent depth, high cover of branching coral, low cover of erect macroalgae, low wave exposure and high surface complexity. Smaller individuals were associated with wide reef flats and high cover of branching coral, whereas larger animals occurred in deeper water with high surface complexity. Multivariate analyses showed this species to be a habitat generalist, sharing much of its niche with an endemic herbivorous gastropod, Tectus pyramis. Future stocking programs should focus on sites with habitats optimal for both adults and juveniles. R. nilotica populations are likely to be especially affected by broadscale stressors that result in declines in live coral cover and substratum complexity and increasing coverage of macroalgae on coral reefs.